KEPEMIMPINAN TRANSPERSONAL KEPALA SEKOLAH DI PENDIDIKAN DASAR - Rola, Fasti; Rambe, Titin Rahmayanti; Armanto, Dian; Yus, Anita (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2023)
The quality of education in elementary schools must be well maintained so that the next generation of a nation with character is formed. One of the factors that greatly influences the quality of education in elementary schools is good leadership. The principal as the main leader in elementary schools has a very important role in managing the school and leading all members of the school. In the last few decades, transformational leadership theory has become one of the most influential leadership models in education. The transformational approach to leadership has long been considered a productive approach. Transpersonal leadership offers a more humanistic and values-centered approach to addressing the complex challenges faced by today's organizations and societies).